Internet Resources: Dissertation/Thesis Study and Writing Pages - Bahşişoğlu, Hatice Kübra (Information World, 2001)
Number of Internet pages and sites that contain knowledge of all sorts increase enormously. Thus the electronic media serve the scientists with further sources of knowledge, which can’t otherwise be covered by printed materials. However, this increasing trend courses a remarkable shift in the questions directed to librarians, on how the Internet documents could be found aut and how they can be used as sources of knowledge by academic type of work. The main reason behind this increased activity is that especially tor thesis and research work, the Internet provides sample number of sites and pages.